Internship prep for accounting students - Mod Arifin, Nur Nariza; Che Hassan, Anita (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Internships are a vital component of accounting education, bridging classroom learning and real-world organisational experience. However, the benefits gained from internships largely depend on students’ readiness, which includes not only academic knowledge but also professional attitudes, ethics, and technical skills. As digital accounting systems and evolving business practices reshape the profession, universities must better align their curricula with industry expectations to ensure graduates are well prepared for workplace demands.